Symposium International sur les Micro-paléontologiques Belges - Mamet, Bernard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary An international conference was held in Belgium, 2-10 September 1974, to discuss a complete revision of the biostratigraphy of the Devonian and Lower Carboniferous. The symposium was held in the field to permit participants to collect from the classic sections of the Dinant synclinorium and the Namur "synclinal". An example of the detailed bio-stratigraphie work that has been done is provided by one section in the Famennian, which has been subdivided into 73 micropaleonto-logical zones-a degree of subdivision even greater than the subdivision of the Cenozoic on the basis of microplankton. Although many of these zones may be of local significance, it is clear that the region visited constitutes a remarkable stratigraphie succession, where subsidence continued for a long time and where practically all mio-geosyncMnai faciès interfinger. Knowledge of the biostratigraphy of this area is well-advanced and it may be expected to serve as a valuable standard of reference. (Summary prepared by the editor).